The Effectiveness Of Problem-Based Learning On Student Achievement In Economic Subject - Agustina, Lisa; Zakaria, Zakaria; Irwan, Irwan; Arfan, Fahmi; Hasanah, Ida; Buang, Nor Aishah; Hussin, Muhammad; Nur, Muhammad (JURNAL SERAMBI ILMU, 2023)
This study aims to identify the effectiveness of problem-based learning (PBL) on achievement in Economic subject. This study uses an unequal control group design, which has been carried out for 10 weeks involving as many as 80 fourth-grade students at SMAN 1 Unggul Baitussalam, Aceh Besar. The samples were divided into the experimental group and the control group. The students in the experimental group took lessons using the PBL module, while students in the control group followed lessons conventionally. The PBL module was built using analysis, design, development, implementation, evaluation (ADDIE model) teaching design and was based on the five PBL phases. The descriptive statistics used were frequency, percent, mean, and standard deviation, while paired t-test, independent t-test, and MANOVA were used to test the hypotheses. The results showed student achievement in the experimental group experienced a significant increase, while students in the control group only experienced a slight increase. The results of the MANOVA showed there was no effect on the test scores of Basic Economics before and after the experiment. At the same time, the results of the study also found there was an interaction effect of achievement levels on test scores before and after the experiment. However, there was no significant interaction effect between groups and achievement level on the test scores before and after the experiment. Overall, the findings of this study indicate that the PBL has had a positive impact on student achievement.